An analysis on the suitability of selected newspaper material as a teaching resource in efl courses. - Torres, María (2010)
The purpose of this research project is to investigate the didactic value and suitability of newspapers as a source to teach not only reading comprehension, but additionally grammar and vocabulary. The most important finding was that in fact, newspapers are a useful tool to teach English because they are authentic texts which are about current events and, when students use them in class they enrich their vocabulary, reinforce their grammar knowledge, and keep them up-dated about what is happening around the world.